PENINGKATAN KEMAMPUAN MENULIS TEKS PROSEDUR DENGAN MODEL PEMBELAJARAN PAIR CHECKS - Ana, Ana (Universitas Tanjungpura, 2018)
This study is aimed to describe the improvement of writing abiliy on procedure text by using pair checks learning model at the eighth grade students of SMP Negeri 1 Sengah Temila. The method used in this research was descriptive method. Descriptive method is concerned with developing or giving explanations of social phenomena towards subject that being observed. The techniques used in this research were observaion, documentary study, and test. The result of writing ability on prosedure text by using pair checks learning model at the eighth grade students of SMP Negeri 1 Sengah Temila in the firstcycle was 72, 88% and in the second cycle, the students’ score was 80, 45%. It can be concluded that the implementation of pair checks learning model improved students’ writing ability on procedure text at the eighth grade students of junior high school in SMP Negeri 1 Sengah Temila.